Perubahan Iklim Berbasis Pendugaan Cadangan Karbon Di Kota Padang Provinsi Sumatera Barat - Triyatno Triyatno; Ratna Wilis; Dilla Angraina (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
The most fundamental problem in this study is the high change of land cover that occurred in the city of Padang into settlements and open land, so that forest cover becomes reduced. If forest cover diminishes, while population, industry and transportation growth is increasing, environmental inequalities from plants absorbing emissions released by human activity decrease, so the surface temperature becomes warmer. If this is allowed to continue, then the hydrometeorological disaster will threaten the city of Padang. In general, this study aims to determine how the phenomenon of climate change that occurred in the city of Padang based on the estimation of carbon stocks in accordance with land cover. This research uses a combination of remote sensing technology with direct measurement in the field. The integration of land cover change data with the value of carbon stocks on a plot scale can illustrate changes in carbon stocks on a landscape scale. The results show that within 1989-2017 there has been a change in forest cover to non-forest land that leads to a decrease in carbon stocks and increased carbon emissions. Increased carbon emissions in the atmosphere caused a change in rainfall in Padang City, where Padang City had a high rainfall ranging from 4500-6000mm / year, while now decreasing to 3000-4500 mm/year indicating that climate change has occurred in Padang City.